2012
DOI: 10.1149/2.097206jes
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Deposition of Highly Conformal Copper Seed Layers for Plating Through-Silicon Vias (TSVs)

Abstract: Through-silicon vias (TSV) will speed up interconnections between chips. Manufacturable and cost-effective TSVs will allow faster computer systems. In this paper, we report the successful formation of seed layers for plating copper TSVs with aspect ratios greater than 25:1. Following the rapid atomic layer deposition (ALD) of a conformal insulating layer of silica inside the silicon vias, manganese nitride (Mn 4 N) is deposited conformally on the silica surface by chemical vapor deposition (CVD). Mn 4 N forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…The q(300 K) value of 125 lX cm is one order of magnitude lower than that of the annealed polycrystalline sample, 2.01 mX cm. 12 This suggests that the present 35-nm-thick Mn 4 N thin film contains far fewer local scattering centers such as impurities, defects, and grain boundaries. The residual resistivity ratio [¼q(300 K)/q(2 K)] was 14.…”
Section: N Epitaxial Thin Filmmentioning
confidence: 83%
“…The q(300 K) value of 125 lX cm is one order of magnitude lower than that of the annealed polycrystalline sample, 2.01 mX cm. 12 This suggests that the present 35-nm-thick Mn 4 N thin film contains far fewer local scattering centers such as impurities, defects, and grain boundaries. The residual resistivity ratio [¼q(300 K)/q(2 K)] was 14.…”
Section: N Epitaxial Thin Filmmentioning
confidence: 83%
“…[30][31] X-ray photoelectron spectra (XPS) of DLE-CVD Co samples deposited at different temperatures are provided in Figure 2d. All spectra are taken after 100 s of 100 eV Ar + sputtering to remove surface contamination.…”
Section: Resultsmentioning
confidence: 99%
“…It means that it is almost impossible to realize the metallization of vertical TSVs with conventional PVD process for HAR vias because of poor step coverage. Even though some researchers has reported that the AR can be higher by additional atomic layer deposition (ALD) process [5,9], or electroplating process [10], the cost and process complexity will increase rapidly.…”
Section: Effects Of Via Taper Anglementioning
confidence: 99%